SILAC-based quantification of TGFBR2-regulated protein expression in extracellular vesicles of microsatellite unstable colorectal cancers - Fricke, Fabia; Michalak, Malwina; Warnken, Uwe; Haußer-Siller, Ingrid; Schnölzer, Martina; Kopitz, Jürgen; Gebert, Johannes (International journal of molecular sciences, 2019)
Microsatellite unstable (MSI) colorectal cancers (CRCs) are characterized by mutational inactivation of Transforming Growth Factor Beta Receptor Type 2 (TGFBR2). TGFBR2-deficient CRCs present altered target gene and protein expression. Such cellular alterations modulate the content of CRC-derived extracellular vesicles (EVs). EVs function as couriers of proteins, nucleic acids, and lipids in intercellular communication. At a qualitative level, we have previously shown that TGFBR2 deficiency causes overall alterations in the EV protein content. To deepen the basic understanding of altered protein dynamics, this work aimed to determine TGFBR2-dependent EV protein signatures in a quantitative manner. Using a stable isotope labeling with amino acids in cell culture (SILAC) approach for mass spectrometry-based quantification, 48 TGFBR2-regulated proteins were identified in MSI CRC-derived EVs. Overall, TGFBR2 deficiency caused upregulation of several EV proteins related to the extracellular matrix and nucleosome as well as downregulation of proteasome-associated proteins. The present study emphasizes the general overlap of proteins between EVs and their parental CRC cells but also highlights the impact of TGFBR2 deficiency on EV protein composition. From a clinical perspective, TGFBR2-regulated quantitative differences of protein expression in EVs might nominate novel biomarkers for liquid biopsy-based MSI typing in the future.